Preparation method and application of breathable and highly stretchable hydrogel

By constructing porous hydrogels through gelatin solution foaming and cold-induced gelation, the problem of difficult control of pores and porosity is solved, and a balance between high porosity and high ductility is achieved, which is suitable for biosignal sensing and flexible wearable devices.

CN120682496APending Publication Date: 2025-09-23FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510986479.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

The existing methods for constructing porous hydrogel structures are complex, and the pores and porosity are difficult to control. The high porosity is inconsistent with high ductility, resulting in poor permeability and decreased tensile strength, which limits the development and application of flexible electrodes.

Method used

The gelatin solution foaming method is combined with cold-induced gelation, and a manual or electric foaming pump is used to construct a porous hydrogel. The porosity and pore size are regulated by the sieve aperture, and the ductility is improved by soaking in salt or salt/glycerol composite solution to form a breathable and highly stretchable hydrogel.

Benefits of technology

A balance between high porosity and high ductility is achieved. The elongation at break of the porous hydrogel is 1.5 times that of the non-porous hydrogel. It has excellent air permeability and conductivity, and is suitable for biosignal sensing and flexible wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120682496A_ABST
    Figure CN120682496A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of breathable and highly stretchable hydrogel. The preparation method comprises the following steps: firstly, foaming a gelatin solution through a foaming pump, and cooling and fixing to form porous hydrogel; and then soaking in a composite solution containing salt of a specific type and concentration to obtain the breathable and highly stretchable hydrogel. The method not only can simply, conveniently and efficiently construct the porous hydrogel with controllable porosity and aperture, but also overcomes the contradiction between the porous structure and high ductility. The obtained hydrogel has excellent air permeability, ductility, electrical conductivity and light weight, and can detect human motion information and electrophysiological signals by being applied to different epidermis positions of a human body. The invention provides a new thought and method for preparing a breathable and comfortable hydrogel flexible electrode, and is beneficial to the development of hydrogel electronic skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of flexible electrode preparation, and more specifically, relates to a preparation method and application of a breathable and highly stretchable hydrogel. Background Art

[0002] With the aging of the population and the increasing health awareness of residents, the demand for real-time monitoring of human physiological signals is growing. Unlike traditional rigid sensors, flexible sensors have attracted widespread attention due to their low Young's modulus, deformability, and conformal contact capabilities. Among them, hydrogels are considered to be excellent flexible sensor substrates due to their excellent biocompatibility and Young's modulus that is compatible with human tissue. Hydrogel-based sensors have been widely used in various biomedical fields, including human motion monitoring, electrophysiological signal detection, tissue regeneration, and neural repair. However, due to their saturated water filling, hydrogels can hinder the exchange of air, moisture, and heat between the skin and the environment, causing sweating at the skin-device interface, resulting in poor wearing comfort, device slippage, and even falling off.

[0003] An effective strategy to improve the permeability of hydrogels is to construct a porous structure for gas and heat to pass through. At present, the porous structure of hydrogels is mainly constructed by emulsion template method, solid particle template method, gas template method and ice template method. The emulsion and solid particle template methods require tedious elution processes, are inefficient and pollute the environment. The ice template method is difficult to operate and the pore structure is difficult to control. The gas template method forms pores by gelation to fix bubbles generated by chemical or biological reactions. It is simple to operate and efficient. However, due to the difficulty in controlling the dual dynamic process of gas generation and gelation and the poor stability of bubbles in the solution, the gas template method has problems such as low porosity, uneven pore distribution and difficult to control pore size. At the same time, the introduction of pores will destroy the integrity and uniformity of the hydrogel structure, thereby accelerating crack formation and expansion, resulting in a decrease in tensile strength. In particular, the contradiction between high porosity and good ductility limits the development and application of porous hydrogel flexible electrodes. Summary of the Invention

[0004] This invention addresses the complexities of constructing porous hydrogel structures, the difficulty in controlling pores and porosity, and the conflict between high porosity and high ductility. By providing a method for preparing breathable and highly stretchable hydrogels, this method is simple and efficient, resulting in hydrogels with high porosity, controllable pore size, and excellent ductility, breathability, and conductivity.

[0005] The first object of the present invention is to provide a simple and efficient method for constructing a porous hydrogel with high porosity and controllable pore size.

[0006] The second object of the present invention is to provide a method for improving the ductility of the porous hydrogel.

[0007] The third object of the present invention is to provide an application of the breathable and highly stretchable hydrogel in biological signal sensing.

[0008] In order to achieve the above objectives, the following technical solutions are adopted: A method for preparing a breathable and highly stretchable hydrogel comprises the following steps: (1) Dissolve gelatin powder in 60°C hot water to obtain a gelatin solution; (2) The gelatin solution obtained in step (1) was kept warm to 40-55 °C, foamed into a silicone mold using a foaming pump, and immediately transferred to -20-4 °C and cooled for 2 h to obtain a porous hydrogel; (3) Cutting the porous hydrogel obtained in step (2) into any shape and soaking it in a salt solution or a salt / glycerol composite solution for 12 to 48 hours to obtain the breathable and highly stretchable hydrogel.

[0009] The concentration of the gelatin solution in step (1) is 5.0-15.0 wt %; The foaming pump in step (2) is a manual foaming pump or an electric foaming pump, wherein the foaming pump head contains 1 to 2 layers of screens, the screen mesh aperture is 10 to 200 μm, wherein the input side aperture is 50 to 200 μm, and the output side aperture is 10 to 100 μm; The salt in the salt solution and the salt / glycerol composite solution in step (3) above is one of sodium citrate, ammonium sulfate, and sodium sulfate, the salt concentration is 15-30 wt%, and the glycerol concentration is 10-30 vol%.

[0010] The obtained breathable and highly stretchable hydrogel is prepared by any of the above methods.

[0011] The above-mentioned breathable and highly stretchable hydrogel is used as a flexible sensor for biological signal sensing, or for drug delivery and wound dressing.

[0012] Compared with the prior art, the present invention has the following advantages: (1) The present invention utilizes the excellent foaming properties and cryogelation ability of gelatin to construct a high-porosity porous hydrogel without the need for additional surfactants; (2) The present invention uses a manual or electric foaming pump for foaming, which is simple to operate and efficient, and the foaming rate, porosity and pore size can be adjusted by the sieve aperture; (3) The hydrogel has both high porosity and high ductility, with an elongation at break that is 1.5 times that of non-porous hydrogel. It also has excellent air permeability and suitable conductivity. It can sensitively monitor human activity signals, detect electrocardiogram signals and electromyography signals, and is expected to be used in fields such as biosensors and flexible wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 Effects of gelatin solution concentration, temperature and mesh size on foaming rate; Figure 2 Tensile stress-strain curves of porous hydrogels after immersion in ammonium sulfate solutions with different concentrations; Figure 3 Tensile stress-strain curves of porous hydrogels after immersion in ammonium sulfate / glycerol composite solutions with different concentrations; Figure 4 Tensile stress-strain curves of porous hydrogels and non-porous hydrogels before (A) and after (B) immersion in ammonium sulfate (25 wt%) / glycerol (30 vol%) composite solution. Figure 5 Optical microscope images and pore size distribution of porous hydrogels with different foaming ratios; Figure 6 Air permeability of porous hydrogels with different foaming rates; Figure 7 Porosity of porous hydrogels with different foaming rates; Figure 8 Water vapor transmission curves of porous hydrogels and other materials; Figure 9 Resistance change curves of the porous hydrogel when monitoring joint motion during finger bending (A), forehand hitting (B), and backhand hitting (C); Figure 10 Porous hydrogels are used as electrode patches to monitor electrocardiographic and myoelectric signals. DETAILED DESCRIPTION

[0014] The present invention will be further described below with reference to the accompanying drawings and specific examples, but the examples do not limit the present invention in any way. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0015] Example 1 Effect of gelatin solution concentration, temperature and foaming net pore size on foaming rate 1. Effect of gelatin solution concentration on foaming rate 7.5, 10.0, 12.5, and 15.0 g of gelatin powder were weighed and dissolved in 92.5, 90, 87.5, and 85 mL of deionized water, respectively. The gelatin solution was stirred magnetically at 60 °C for 30 min to completely dissolve. The gelatin solution was transferred to a 40 °C water bath and kept warm for 30 min. The solution was then foamed into a silicone mold (3 × 3 × 3 cm) using a foaming pump. 3 , the same below), the pore sizes of the input side mesh (IPM) and the output side mesh (OPM) of the foaming pump are 100 μm and 70 μm, respectively.

[0016] 2. Effect of gelatin solution temperature on foaming rate Weigh 10.0 g of gelatin powder and dissolve it in 90 mL of deionized water. Dissolve completely at 60°C with magnetic stirring for 30 min. Transfer the gelatin solution to a water bath at 40, 45, 50, and 55°C for 30 min. Then, use a foaming pump with 100 μm IPM and 70 μm OPM, respectively, to foam onto a silicone mold.

[0017] 3. Effect of OPM on Foaming Rate Weigh 10.0 g of gelatin powder and dissolve it in 90 mL of deionized water. Stir magnetically at 60°C for 30 minutes to completely dissolve the gelatin solution. Transfer the gelatin solution to a 40°C water bath and incubate for 30 minutes. Then, use a foaming pump with OPMs of 10, 30, 50, and 70 μm, respectively, and an IPM of 100 μm, to foam the solution onto a silicone mold.

[0018] 4. Effect of IPM on Foaming Rate Weigh 10.0 g of gelatin powder and dissolve it in 90 mL of deionized water. Stir magnetically at 60°C for 30 minutes to completely dissolve the gelatin solution. Transfer the gelatin solution to a 40°C water bath and incubate for 30 minutes. Then, use a foaming pump with an OPM of 30 μm and IPMs of 50, 100, 150, and 200 μm, respectively, to foam the gelatin onto a silicone mold.

[0019] The foamed gelatin solution was transferred to -20 °C and frozen for 2 h to obtain a porous gelatin hydrogel. The weight of the silicone mold before and after foaming was weighed to calculate the weight and corresponding volume of the gelatin solution. The volume of the porous hydrogel after gelation was measured using a vernier caliper to calculate the foaming rate of the gelatin solution. Figure 1 As shown in the figure, as the gelatin solution concentration increases from 7.5 wt% to 15.0 wt%, the foaming rate first increases and then decreases, reaching a maximum of 3.90 at 10.0 wt%. The foaming rate of the gelatin solution decreases as the solution temperature increases from 40 °C to 55 °C. As the OPM increases from 10 μm to 70 μm, the foaming rate of the gelatin solution first increases and then decreases, reaching a maximum at 30 μm, while it decreases as the IPM increases from 50 μm to 200 μm. Specifically, when the gelatin solution concentration is 10 wt%, the temperature is 40 °C, and the OPM and IPM are 30 μm and 50 μm, respectively, the foaming rate reaches a maximum of 5.19.

[0020] Example 2 Effects of Ammonium Sulfate Concentration and Ammonium Sulfate / Glycerol Concentration on the Tensile Properties of Porous Hydrogels 10.0 g of gelatin powder was weighed and dissolved in 90 mL of deionized water. The solution was magnetically stirred at 60 °C for 30 min to completely dissolve. The gelatin solution was transferred to a 40 °C waterbath and incubated for 30 min. It was then foamed onto a silicone mold using a 30 μm OPM and 50 μm IPM foaming pump. The unfoamed gelatin solution was molded into the same silicone mold to form a nonporous hydrogel. After freezing at -20 °C for 2 h, the solidified porous hydrogel was cut into 50 mm × 20 mm × 2 mm strips. The porous hydrogel was then immersed in ammonium sulfate solutions with concentrations of 15 wt%, 20 wt%, 25 wt%, 30 wt%, and 35 wt%, or in an ammonium sulfate / glycerol composite solution with ammonium sulfate concentrations of 20 wt%, 25 wt%, and 30 wt% and glycerol concentration of 30 vol% for 24 h to obtain breathable and highly stretchable hydrogels. After absorbing the soaking solution absorbed in the porous hydrogel, the tensile properties of the hydrogel were tested using a universal testing machine. The sample that had not been soaked was used as a control. Figure 2 As shown in Figure 2, for samples immersed in ammonium sulfate solution, as the concentration of ammonium sulfate increases from 15 wt% to 35 wt%, the tensile strength of the porous hydrogel gradually increases, while the elongation at break first increases and then decreases, reaching a maximum value when the concentration of ammonium sulfate is 20 wt%. Figure 3 As shown in Figure 2, for samples immersed in ammonium sulfate / glycerol composite solution, as the ammonium sulfate concentration increases from 20 wt% to 30 wt%, the tensile strength of the porous hydrogel gradually increases, while the elongation at break first increases and then decreases, reaching a maximum value when the ammonium sulfate concentration is 25 wt% and the glycerol concentration is 30 vol%. Figure 4 As shown in (A), compared with the unsoaked sample, the elongation at break of the porous hydrogel after soaking in ammonium sulfate (25 wt%) / glycerol (30 vol%) composite solution increased by more than 8 times, indicating that soaking in ammonium sulfate / glycerol composite solution can improve the mechanical properties of the porous hydrogel. Figure 4 As shown in (B), the elongation at break of the porous hydrogel soaked in ammonium sulfate / glycerol composite solution is about 1.5 times that of the non-porous hydrogel, indicating that the porous hydrogel has excellent ductility, even better than the non-porous hydrogel.

[0021] Example 3 Effect of Foaming Rate on the Porous Structure and Air Permeability of Porous Hydrogels 10.0 g of gelatin powder was weighed and dissolved in 90 mL of deionized water. The solution was stirred magnetically at 60°C for 30 min to completely dissolve. To prepare samples with a foaming rate of ~3x, the gelatin solution was transferred to a 55°C water bath and incubated for 30 min. The solution was then foamed onto a silicone mold using a 70 μm foaming pump for OPM and a 100 μm foaming pump for IPM, respectively. To prepare samples with a foaming rate of ~4x, the solution was transferred to a 40°C water bath and incubated for 30 min. The solution was then foamed onto a silicone mold using a 70 μm foaming pump for OPM and a 100 μm foaming pump for IPM, respectively. To prepare samples with a foaming rate of ~5x, the solution was transferred to a 40°C water bath and incubated for 30 min. The solution was then foamed onto a silicone mold using a 30 μm foaming pump for OPM and a 50 μm foaming pump for IPM, respectively. The porous gelatin hydrogels with different foaming rates were frozen at -20°C for 2 h and cut into 0.5 cm thick slices. After being immersed in a composite solution with an ammonium sulfate concentration of 25 wt% and a glycerol concentration of 30 vol% for 24 h, the solution adsorbed in the porous hydrogel was dried.

[0022] Use an optical microscope to observe the microstructure of the porous hydrogel, measure the pore size, and draw a pore size distribution diagram. Figure 5 As shown in the figure, all porous hydrogels are composed of a large number of uniform pores, and the pore size is normally distributed. As the foaming ratio increases from 3 to 5, the pore size distribution of the porous hydrogel tends to be concentrated, and the pore size first increases and then decreases.

[0023] The air permeability of porous hydrogels was determined according to the method of GB / T 5453-1997, and the water vapor transmission curves of porous hydrogels and other common materials were determined. Figure 6 As shown in Figure 3, as the foaming rate increases from 3 to 5, the air permeability of the porous hydrogel gradually increases.

[0024] like Figure 8 As shown in the figure, the water vapor transmission rate of the porous hydrogel is higher than that of the non-porous hydrogel, gauze, and polyethylene film, and is only lower than that of the open state. These results show that the present method achieves a balance between high porosity and high ductility of the porous hydrogel. Under the optimal process parameters, that is, solution concentration of 10 wt%, foaming temperature of 40 °C, OPM of 30 μm, IPM of 50 μm, and after being foamed in ammonium sulfate (25 wt%) / glycerol (30 vol%) composite solution, the prepared porous hydrogel has a high porosity of 0.66 (such as Figure 7 (shown) with a ductility of up to 4.68 mm -1 Furthermore, the porous hydrogel prepared by this method has excellent gas and water vapor permeability.

[0025] Example 4 Application of Breathable and Highly Stretchable Hydrogels in Biosensing 10.0 g of gelatin powder was weighed and dissolved in 90 mL of deionized water. The solution was stirred magnetically at 60°C for 30 min to completely dissolve. The gelatin solution was transferred to a 40°C water bath and incubated for 30 min. The solution was then foamed onto a silicone mold using a 30 μm OPM and 50 μm IPM foaming pump. After freezing at -20°C for 2 h, the solidified porous hydrogel was cut into 1 cm thick sheets or arbitrary shapes. The gelatin porous hydrogel was immersed in an ammonium sulfate / glycerol composite solution containing 25 wt% ammonium sulfate and 30 vol% glycerol for 24 h to obtain a breathable and highly stretchable hydrogel. The absorbed immersion solution was then blotted off the porous hydrogel. The high concentration of salt ions introduced into the ammonium sulfate / glycerol composite solution imparted electrical conductivity to the hydrogel.

[0026] like Figure 9 As shown in the figure, by attaching the porous hydrogel to the finger joint, the resistance change caused by finger bending can be cyclically and stably monitored, thereby determining the finger bending angle. By attaching the hydrogel to the elbow, the movement of the volunteer's elbow in table tennis can be identified by monitoring the resistance change to determine whether the athlete is hitting the ball forehand or backhand. Figure 10 As shown, the porous hydrogel patch can transmit electrophysiological signals and realize the detection of electrocardiogram (ECG) and muscle electrical signals (EMG).

[0027] The above embodiments are preferred implementations of the present invention, but the implementations of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered equivalent replacement methods and are included in the scope of protection of the present invention.

Claims

1. A method for preparing a breathable and highly stretchable hydrogel, characterized in that: The following steps are involved: (1) Dissolve gelatin powder in 60°C hot water to obtain a gelatin solution; (2) The gelatin solution obtained in step (1) was kept warm to 40-55 °C, foamed into a silicone mold using a foaming pump, and immediately transferred to -20-4 °C and cooled for 2 h to obtain a porous hydrogel; (3) Cutting the porous hydrogel obtained in step (2) into any shape and soaking it in a salt solution or a salt / glycerol composite solution for 12 to 48 hours to obtain the breathable and highly stretchable hydrogel.

2. The method for preparing a breathable and highly stretchable hydrogel according to claim 1, wherein: The concentration of the gelatin solution in step (1) is 5.0-15.0 wt%.

3. The method for preparing a breathable and highly stretchable hydrogel according to claim 1, wherein: The foaming pump in step (2) is a manual foaming pump or an electric foaming pump, wherein the foaming pump head contains 1 to 2 layers of screens, the screen mesh aperture is 10 to 200 μm, wherein the input side aperture is 50 to 200 μm, and the output side aperture is 10 to 100 μm.

4. The method for preparing a breathable and highly stretchable hydrogel according to claim 1, wherein: The salt in the salt solution and the salt / glycerol composite solution in step (3) is one of sodium citrate, ammonium sulfate, and sodium sulfate, the salt concentration is 15-30 wt%, and the glycerol concentration is 10-30 vol%.

5. A breathable and highly stretchable hydrogel prepared according to the method of any one of claims 1 to 4.

6. Use of the breathable and highly stretchable hydrogel according to claim 5, characterized in that: Breathable and highly stretchable hydrogels can be used as flexible sensors for sensing human motion behavior and electrophysiological signals, or in drug-carrying and antibacterial wound dressings.